Hacia un sistema de gestión ambiental como parte del marco regulatorio de las gasolineras en México (Tema Central) - Canobbio Rojas, Claudia (2020)
Although awareness of the environment represents opportunities for entities that are governed by an ecological conscience, such transition towards corporate environmental management also sets challenges. Through a mixed methodological approach, a documentary and analytical investigation is projected, as well as a survey of different actors involved, with the objective of analysing the process of setting up an environmental management system through which the service stations of public gasoline and diesel (gas stations) in Mexico are, under the new regulatory framework of the national energy reform. Through the findings of this study, it is possible to elucidate how, in the name of the environment, these legal requirements go into regulating new and various aspects of the management of this kind of firms, such as the implementation of the so-called Industrial Security Administration System, Operational Safety and Environmental Protection (SASISOPA). These approaches, under the theoretical approach of the Deming cycle, make it possible to know the formulation and implementation of quality improvement projects for service stations and their functional relationship with obtaining external advice.